1995
DOI: 10.1111/j.1095-8649.1995.tb05953.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural responses of sablefish, Anoplopoma fimbria, to bait odour

Abstract: A behavioural bioassay was used to determine the response threshold to squid extract of sablefish, Anoplopoma fimbria, held at three different feeding regimens. Sablefish responded to the odour of bait by changing swimming activity and turning behaviour. The response threshold to bait odour was influenced by both the amount of food eaten and the duration of food deprivation. The total concentration of amino acids in the bait extract was assumed to determine the response threshold as chemical fractionation stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 27 publications
1
45
0
1
Order By: Relevance
“…A. fimbria are capable of sustaining long periods of food depravation (Sullivan & Smith 1982), likely an adaptation to the periodic nature of food availability in the deep sea. Lokkeborg et al (1995) demonstrated that response to a low-concentration odor plume was higher in food-deprived A. fimbria, whereas satiated individuals spent the majority of their time resting on the bottom, away from the light during periods of exposure to odor plumes. We propose that the observed A. fimbria behavior around our baited camera was the result of competing sensory inputs.…”
Section: Discussionmentioning
confidence: 97%
“…A. fimbria are capable of sustaining long periods of food depravation (Sullivan & Smith 1982), likely an adaptation to the periodic nature of food availability in the deep sea. Lokkeborg et al (1995) demonstrated that response to a low-concentration odor plume was higher in food-deprived A. fimbria, whereas satiated individuals spent the majority of their time resting on the bottom, away from the light during periods of exposure to odor plumes. We propose that the observed A. fimbria behavior around our baited camera was the result of competing sensory inputs.…”
Section: Discussionmentioning
confidence: 97%
“…Ž Many behavioural bioassays have been designed Carr and Chaney, 1976;Mearns, . 1985;Løkkeborg et al, 1995 . Such methods can be used to test a large number of stimuli within short periods.…”
Section: Discussionmentioning
confidence: 99%
“…Fish with low condition factor, i.e. thin fish, probably have higher nutritional requirements and thus higher feeding motivation (Løkkeborg et al, 1995). It is likely that these fish are caught in higher proportions by longline, which exploits the feeding behaviour of the target fish.…”
Section: Comparisons Of Gearsmentioning
confidence: 99%